Rancang Bangun Sistem Informasi Penerimaan dan Pembayaran Peserta Didik Baru Di SMA Yadika Cicalengka - Dena Meilanda; Ayi Mirazul Mu’minin; Kanda M. Ishak (Ma'soem University, 2022)
The ongoing registration system is still manual, where prospective students come directly to the school to register by bringing the requirements that have been determined by the school then fill out the form and make payments immediately, there are two ways of paying, namely cash and installments, after that the officer recaps the data all registrants and enter it into the ppdb book manually, then the officer inputs the data into microsoft excel for it to be printed to produce registration slips and reports. The purpose of this Final Project is to anticipate deleted/edited data, facilitates in finding acceptance data in making acceptance reports. The design of this system uses SDLC (Systems Development Life Cycle) with the Waterfall method. The Waterfall model is one of the SDLC models that is often used in the development of information systems or software. This model uses a systematic and sequential approach. The stages in this model start from the planning stage to the maintenance stage and are carried out in stages.